Communication is The Key: Does Strategic Perioperative Counseling Decrease Anxiety in Parents of The Pediatric Patient Undergoing Surgery? - Arjyal, Batsalya; Kumar Rajbanshi, Lalit; Khanal, Kanak; Man Singh, Dipesh; Pathak, Hiramani; Sangroula, Rakshya (Birat Journal of Health Sciences, 2024)
Introduction: Anxiety is very common during the perioperative period. Anxiety among the parents of pediatric patients undergoing surgery is also encountered frequently despite the preoperative counseling which is a common standard of practice. The aim of the study was to determine the effectiveness of strategic perioperative counseling to relieve the anxiety among the parents of pediatric patient posted for surgery. Objectives: To measure the impact of the implemented communication strategies on anxiety levels experienced by parents. Methodology: This is a randomized observational cross-sectional study. After the approval of IRC, A total of 100 samples was chosen. The samples were randomly divided into two groups, control group (group1) and intervention group (group 2). The control group were counselled as per standard practice at preoperative time. The intervention group were counseled at 3 points namely preoperative, intraoperative and postoperative). The beck anxiety inventory score (Nepali version) will be handed to the family members of the patient undergoing pediatric surgery to be filled post operatively. Results: The intervention group where the family members received strategic counselling had lower anxiety scores than the group which received only standard counselling (preoperative). The education level of the sample was also correlated. The data suggests that higher education level had lower anxiety score than the ones who had lower education level. Conclusion: We conclude that strategic perioperative counseling decreases the anxiety among the parents of pediatric patient undergoing surgery.